HUBUNGAN GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI DENGAN KINERJA APARATUR PENDIDIKAN NONFORMAL DI DINAS PENDIDIKAN KOTA GORONTALO - Rahmat, Abdul (Universitas Kristen Satya Wacana, 2015)
This study aimed to examine the alleged causality between the dependent and independent variables. This study is a descriptive research using survey method. Datan collected by using questionnaire and analyzed using path analysis to test the hypothesis. Engineering analysis will be determined by SPSS data analysis program. The result of the study were; 1) Leadership style has a significant relationship with the performance of officials local government in Gorontalo city. It is seen in the calculation of the product r correlation counted is 0.811 at the significance level (0.05), r table at 0,239 then count r > r of the table so that we can conclude the existence of a significant relationship, while the relationship is based on arithmetic interval coefficient criteria r is 0.811, which means relatively strong relationship with the leadership style of performance in local government apparatus city Gorontalo relatively strong. While t is 0.957 and compared t table with a significance level of 0.044 (0.05) turns out t count> t table with the sense of the hypothesis is accepted which stated the existence of a significant relationship. 2) Organizational Culture has a significant relationship performance in local government apparatus city Gorontalo, it can be seen that the calculation of the product correlation r counted is 0.922 at the significance level (0.05)r price table is 0.098 then the count r > r table. It conclude the existence of a significant relationship, while the relationship is based on interval arithmetic coefficient criteria r is 0.922, which means has relatively strong relationship with the organizational culture apparatus as very strong performance. While t is 0.957 and compared t table with a significance level of 0.044 (0.05) turns out t > t table. It means the hypothesis is accepted which states the existence of a very significant. 3) Relationship between Leadership Style and organizational culture have significant performance relationship in local government of Gorontalo apparatus city. It is seen in the strength of mastery skills and cultural organization along with the performance of the apparatus, comparing the r counting with r table it is known that 0.811 > 0.239, the correlation both have strong significant relationship.